Faktor Dominan Perilaku Berisiko terhadap Melahirkan Usia Anak - Aprina Aprina; Titi Astuti (Politeknik Kesehatan Tanjung Karang, 2020)
The impact of early marriage, among others, is related to reproductive health. Lampung Province is 10.70% and is the 12th of 22 provinces where the prevalence of child marriage is still above the national average. The purpose of this study is to determine the risk behavior of giving birth to teenagers in Tanggamus Regency in 2020. This type of research is quantitative, analytical research design with a cross-sectional approach. Data analysis was univariate, bivariate, and multivariate. The results of the study were 132 (53,7%) respondents with good knowledge, 143 (58,1%) respondents with a positive attitude, 149 (60,6%) respondents with higher education, 164 (66,7%) %) respondents with sufficient economic status, as many as 168 (68.3%) respondents with premarital sex, as many as 78 (31,7%) respondents with a positive physical environment, as many as 133 (54,1%) respondents with positive beliefs, as many 140 (56,9%) respondents with a positive role as an officer, as many as 137 (55,7%) respondents with a negative parent role, as many as 176 (71,5%) respondents with a positive socio-cultural role, as many as 164 (66,7%) respondents who did not give birth to the age of the child. There is a relationship between knowledge, attitudes, economic status, premarital sex, physical environment, beliefs, and customs on the behavior of giving birth to teenagers. There is no relationship between the role of health workers, the role of parents on the behavior of giving birth to adolescents, the dominant factor in giving birth to children in Tanggamus Regency in 2020 is premarital sex.